British Edition of the Monroe Doctrine versus ‘Com- munist Militarism’: Collisions between the USSR and the UK in Eastern Countries in the mid-1920s - E. Yu. Sergeev (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика)
The new US foreign policy concept in the Western hemisphere introduced by the American President J. Monroe in December 1823 has become a milestone both in the country’s history and in the theory and practice of international relations in general. For Great Britain, the principles of the Monroe Doctrine acquired new relevance after the end of the First World War. The prospect of unfettered Bolshevik expansion into British colonies and dependent territories in Asia and Africa became a matter of particular concern for the UK ruling circles. It was this threat that forced the military and political elites of Great Britain to turn to the experience of their overseas counterparts and develop a set of measures that can be described as the British edition of the Monroe Doctrine. These measures were directed right against the Bolsheviks’ attempts to revolutionize the national liberation movement and to use it to undermine the ‘colonial rear’ of the imperialist powers. British decision-makers interpreted these attempts as a Bolsheviks’ endeavor to revive the foreign policy practices of the Russian Empire and denoted them as ‘communist militarism’. It is through the lens of the collision of the British edition of the Monroe Doctrine and the concept of ‘communist militarism’ that this study examines the dynamics of the Soviet-British confrontation in Central Asia in the mid-1920s. Special attention is paid to the struggle that took place between the two countries in Iran (Persia), Afghanistan, northwest India, Xinjiang and Tibet. This competition for influence over local rulers took a variety of forms: from information and propaganda campaigns to rivalry in the field of infrastructure and logistics projects. At the same time, it was accompanied by a constant clash of interests of various factions within the USSR and Great Britain, which prevented them from pursuing a coherent policy in the region. Together, these circumstances endowed the Soviet-British rivalry in Central Asia in the 1920s with a number of unique features that does not allow it to be interpreted as just yet another round of the ‘Great Game’.